A Christian Education Approach for Early Childhood in the Disruptive Era - Alexa Clara Ngayow; Orient Christianty; Febri Kurnia Manoppo (ADI Publisher, 2020)
Christian Education for Early Childhood faces a real challenge with the presence of gadgets as products that are very attractive to everyone in the virtual world. Adults to early childhood now enjoy the presence of gadgets and all the conveniences they offer. The impact of the era of disruption as part of digitalization in the industrial revolution must be addressed properly by teachers, and parents who have early childhood. Based on this background the author wants to examine and describe about how the approach to Christian education applied by teachers and parents to educate young children in this era of disruption? A qualitative approach was used in this research with the method of observation, interviews, and study documentation. This research is expected to be useful to increase the treasury of scientific theories about Christian education approaches for Early Childhood which have been taking place in the era of disruption.